Military Politics in Indonesia (Birth of the Political Program for the Indonesian National Armed Forces) - Aditya Dwiputra; Fathan Al-Kautsar; Lucky Luciana; Salsa Fadilah (Social Impact Journal, 2022)
The political dimension as well as the military dimension is a problem faced by the Indonesian National Armed Forces (TNI). The source of political disturbance is based on the communist faction that wants to place the Indonesian National Armed Forces (TNI) under the influence of their power. The birth of a political program is marked by the unity of the armed forces under one command in the hope of achieving effectiveness and efficiency in carrying out its role. A new challenge was faced by a TNI when the 30 September Movement (G30S) occurred. This happened during a political turmoil that occurred in 1998 and had an impact on ABRI institutions, until finally on April 1, 1999. TNI's political participation from time to time is massive enough that we can find it in political and state realities. Bearing in mind that the existence of the TNI, especially retired officers, currently often adorns the ranks of the state bureaucracy or party elites in Indonesia. Because of this agreement, of course, we also cannot just let go of how and what are the criteria for the TNI to enter government ranks through political education to increase the competence of TNI soldiers who want to enter the realm of national politics.